Multiple Myeloma Breast Involvement: A Case Report - Heba O. E. Ali; Zafar Nasir; Ahmed M. S. M. Marzouk (Case Reports in Radiology)
Multiple Myeloma involving the breast is very rare and the diagnosis is challenging because the clinical and radiological features of breast multiple myeloma are indistinguishable to other forms of breast disease whether primary or metastatic. In this article the authors report a case presented with breast masses, which were found to be extra osseous Multiple Myeloma. The patient was managed for multiple spinal lesions that were primarily thought to be metastasis from primary breast cancer.